Tipe Habitat Kesukaan Rusa Timor (Rusa timorensis) di Hutan Wanagama I - Danang Wahyu Purnomo; Djuwantoko Djuwantoko; Satyawan Pudyatmoko (Universitas Atma Jaya Yogyakarta, 2010)
Wanagama I Forest (599.7 ha) is a research and education forest which is the habitat of Timor Deer (Rusa timorensis). The deer population has been breeding naturally. The habitat changes have affected to the deer in selecting the resources in its habitat and have caused the deer moving out from the forest to the more strategic area, i.e. agricultural and settlement. We suspected that the case happened because of the habitat quality degradation in the forest. The research was aimed to identify habitat types preferred by deer that were called Habitat Preference. Habitat preference was analyzed by habitat selection that was estimated using habitat-categorizing approaches (Alldredge, Thomas, and Mcdonald, 1998; Manly et al., 2002). Habitat selection was identified by chi-square test and the preference index was estimated by selection ratio index. The result of habitat-categorizing analysis showed that there was a habitat selection by the deer (chi-square test X2=15.23, α=0.05). Block 5 (selection standardized index, B=0.220), Block 17 (B=0.212), and Block 14 (B=0.149) were the habitat types which had high probability selected by the deer for their activities.